Does women's higher education reduce wage inequality? Evidence from Palestine using repeated cross-sectional data - Morar, Najiba; Awawda, Sameera (Springernature, 2024)
Despite the increase of the share of highly-educated women, gender wage gap remains an ongoing issue in developing countries. The increase in women's education would provide them with more job opportunities resulting in higher employment rate amongst women and, thus, lower gender pay gap. In Palestine, the share of women with high education is 62% while their labor force participation rate is only 18%. This paper examines the effects of gender higher education on wage inequality in the Palestinian context. The study applied the Mincer equation to study the determinants of wage, while the decomposed Gini coefficient is used to measure the contribution of education and other factors to overall wage inequality. The study used data from the labor force survey (LFS) which is conducted by the Palestinian Central Bureau of Statistics (PCBS) covering the period from 2010 to 2020. Results show that those with higher education have relatively higher wages as compared to those with only high education or with school education. Results also show that gender wage inequality has increased during the study period (2010-2020), but the contribution of both gender and education differences to the overall wage inequality has decreased. In general, the gender pay gap remains a crucial issue in the Palestinian context with a persisting decreasing pay gap over time across all education levels. Policymakers shall orient efforts towards investing in women's education, thus increasing their empowerment in the labor market, which in turn would improve the level of development and economic growth in the country.
Keywords: Income Inequality; Decomposition; Countries; Impact